Emotional aspects of home-based patients using urinary catheters: a scoping review - Santos, Gabriel Xavier; Itao, Patrícia Malagutti Meneghetti; Soldera, Andrezza Gabrielly dos Santos; Soares, Adson Hugo Gonçalves; Mazzo, Alessandra (O Mundo da Saúde, 2024)
To identify, synthesize, and analyze the scientific knowledge produced on the emotions of home-based patients using indwelling and intermittent urinary catheters. A scoping review following the Joanna Briggs Institute’s approach. The Population, Concept, and Context (P - home-based, bedridden patients; C - emotions; C - using indwelling/intermittent urinary catheter) strategy was used to formulate the guiding research question. The search was conducted from February 19 to 25, 2024, in the National Library of Medicine (PubMed/MEDLINE), Scopus, Embase, Web of Science, Scientific Electronic Library Online (SciELO), LILACS, and CINAHL with Full Text. Of the 56 articles found, 11 were included in the study for meeting the established inclusion criteria. The 11 studies identified were published over the last four decades and report positive or negative emotions related to the use of indwelling urinary catheters, such as confidence, empowerment, fear, embarrassment, pain, discomfort, aversion, depression, grief, loss, suffering, distress, limitations, changes in sexual activities, and body image. Qualified professionals knowledgeable about public policies that can better ensure a support network for these patients may have a greater impact on their care.